GAMBARAN GANGGUAN HEMOSTASIS PADA PENDERITA SIROSIS HATI YANG DI RAWAT DI RSUP PROF.DR.R.D.KANDOU PERIODE AGUSTUS 2013 – AGUSTUS 2015 - Saragih, Garry G.; Waleleng, Bradley J.; Haroen, Harlinda (Universitas Sam Ratulangi, 2016)
Abstract: Liver cirrhosis is a chronic disease characterized by changes in the structure and architecture of the liver parenchyma resulting in liver dysfunction. One of the liver dysfunction is changes in metabolism of proteins that play a role in blood clotting hemostasis). Therefore, one of the complications often found in liver cirrhosis is bleeding. This study aimed to obtain the profile of hemostatic disorder of cirrchosis patients treated in Prof. Dr. R. D. Kandou Hospital Manado from August 2013 toAugust 2015. This was a retrospective descriptive study using the secondary data of the Medical Record. The results showed that there were 75 patients with liver cirrhosis; 34 (45.7%) had impaired hemostasis. The highest proportion of cirrhotic patients with hemostasis disorder was male (67.6%); age group of 51-65 years (55.8%); the most common cause was HBV infection (35.3%); the most often bleeding manifestation was melena (61.7%); and the most common cause of bleeding was esophageal varices (44.1%), prolongation of PT (86.7%) and of APTT (46.7%). Low level of platelets count occured in 85,2% of patients. Conclusion: Almost half of the patients with liver cirrhosis had hemostasis disorders. Prolongation of PT occurred in most of the patients, however, no significant APTT prolongation was found. Thrombocytopenia frequently occured in patients with liver cirrhosis associated with hemostasis disorders. Keywords: hemostatic disorder, PT, thrombocytopenia, cirrchosis Abstrak: Sirosis hati adalah penyakit hati kronis dimana terjadi perubahan struktur dan arsitektur dari parenkim hati sehingga hati tidak dapat berfungsi dengan baik. Salah satu fungsi hati yang terganggu ialah metabolisme protein yang berperan dalam mengatur fungsi pembekuan darah (hemostasis). Salah satu komplikasi yang sering dijumpai pada sirosis hati adalah perdarahan. Penelitian inin menggunakan metode retrospektif dengan mengambil data sekunder di Instalasi Rekam Medik RSUP Prof. Dr. R. D. Kandou Manado. Dari hasil penelitian diperoleh pasien sirosis hati sebanyak 75 orang, dan 34 orang (45,7%) diantaranya mengalami gangguan hemostasis. Proporsi tertinggi pasien sirosis disertai gangguan hemostasis ialah laki-laki (67,6%); kelompok umur 51-65 tahun (55,8%); penyebab terbanyak infeksi HBV (35,3%); manifestasi perdarahan yang sering muncul ialah melena (61,7%) dengan penyebab perdarahan tersering adalah varises esofagus (44,1%); serta pemanjangan PT (86,7%) dan APTT (46,7%). Nilai trombosit dibawah normal (trombositopenia) terjadi pada 85,2% pasien. Simpulan: Hampir setengah pasien sirosis hati mengalami gangguan hemostasis. Pemanjangan PT terjadi pada sebagian besar pasien yang diperiksa sedangkan pemanjangan APTT tidak signifikan. Trombositopenia sering terjadi pada pasien sirosis hati disertai gangguan hemostasis. Kata kunci: Gangguan hemostasis, PT, trombositopenia, sirosis.